La complejidad antropológica en la articulación entre conocimiento y apetito - Méndez, Julio Raúl (Sapientia, 2008)
At the turn of the 20th century, many thinkers and movements highlighted man’s spirituality and uniqueness in reaction to the positivist trends. It was a quest to find what is more specific in man, his place in the universe. In doing so, many elements from the Judeo-Christian tradition were recovered. Nevertheless some limitations can be observed. According to the author, Thomas Aquinas’ thought offers some important concepts, which allow us to understand the human being’s complexity. Some of these concepts are: esse commune, the analogy of being, and participation. With them, it is possible to understand man’s corporal and spiritual unity, and other aspects of the human nature, such as the relation between reason and tendencies.